Synthesis, properties and self-polymerization of 1, 8-naphthalimide-based vinyl monomer. (21st November 2016) - Gudeika, Dalius; Peciulyte, Laura; Grazulevicius, Juozas V.; Obushak, Mykola D.
ABSTRACT: 1, 8-Naphthalene imide with reactive vinyl group was synthesized by Suzuki reaction. Self-polymerization of the compound starts at 177°C as confirmed by differential scanning calorimetry. The electron affinity values of the monomer and the polymer were found to be −3.30 eV and −3.05 eV, respectively. The solid state ionization potential values of the monomer and the polymer were recorded to be 6.42 eV and 6.17 eV, respectively. The activation energy of the process was estimated using Ozawa method. It depends on the conversion degree and was found to be in the range of 136-195 kJ/mol. Pre-exponential factor values decrease during polymerization with decreasing chain mobility due to increasing molecular weight of the polymer.